Research adavances of podocyte damage mechanism and traditional Chinese medicine intervention in diabetic kidney disease - Wen Xiao-chen; Gong Cheng-jun; Ma Xiao-yan (Linchuang shenzangbing zazhi)
Diabetic kidney disease（DKD）is the primary cause of chronic kidney disease and end-stage renal disease and the pathogenesis has remained elusive.Podocyte injury plays a key role in the occurrence and development of DKD.This review summarized the mechanism of podocyte injury in DKD from the aspects of metabolic disorders,oxidative stress,inflammatory response and autophagy disorders and the targets and pathways of traditional Chinese medicine intervention.The goal was provides new ideas and references for researches of traditional Chinese medicine in the prevention and treatment of DKD.